2017
DOI: 10.1097/brs.0000000000002146
|View full text |Cite
|
Sign up to set email alerts
|

Age-Adjusted Alignment Goals Have the Potential to Reduce PJK

Abstract: 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
174
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 232 publications
(202 citation statements)
references
References 33 publications
6
174
2
1
Order By: Relevance
“…There is growing consensus that more judicious, ageappropriate sagittal plane deformity correction might help reduce the incidence of PJK. 9 Other strategies to reduce PJK include cement augmentation at or above the upper instrumented vertebrae (UIV) and a "soft landing" at the top of the construct. [10][11][12][13][14][15][16][17] None of these approaches, however, address the posterior ligamentous structures (PLS) at the UIV.…”
Section: Introductionmentioning
confidence: 99%
“…There is growing consensus that more judicious, ageappropriate sagittal plane deformity correction might help reduce the incidence of PJK. 9 Other strategies to reduce PJK include cement augmentation at or above the upper instrumented vertebrae (UIV) and a "soft landing" at the top of the construct. [10][11][12][13][14][15][16][17] None of these approaches, however, address the posterior ligamentous structures (PLS) at the UIV.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, age should be considered when planning a deformity correction, as older patients tolerate a higher degree of sagittal imbalance and overcorrection beyond age-adjusted targets contributes to proximal junctional kyphosis. 15 Our results should be considered in the context of many limitations. First, because of the retrospective nature, the patients were not matched or randomized and thus, are subject to selection bias and confounding.…”
Section: Discussionmentioning
confidence: 92%
“…308). 14 In a prospective study, Lafage et al 15 found PT and SVA correlated with HRQOL measures, but found the most significant correlations with T1SPi. 4 Thus, correction of SVA, PT, LL-PI, and T1SPi have become primary objectives of adult spinal deformity surgery.…”
Section: Discussionmentioning
confidence: 97%
“…To achieve balance, the demand on the paraspinal muscles to maintain spinal stability naturally increases, and it becomes reasonable to assume that these patients will have greater back pain or fatigue in the sitting position. Proposed age-adjusted and sitting values for sagittal realignment surgeries may further in uence future surgical strategies [18][19][20] .…”
Section: Discussionmentioning
confidence: 99%